Responsiveness of the Investment Office and One-Stop Integrated Services of East Luwu Regency in the Service of Trade Business Licenses - Joyakin Damanik; Sangkala Sangkala; Agus Santosa (Publikasi Indonesia, 2024)
The responsiveness of the Trading Business License (SIUP) licensing service provider is very important to create a pleasant and excellent licensing service system. Simplification of the number and types of licensing and non-licensing has been carried out, from 142 types to 34 types. Through the online system, it is easier for applicants to register and monitor the flow of permits and can speed up the licensing process time, one day service. The Department of Investment and One Stop Integrated Services (DPMPTSP) has made various efforts to increase the responsiveness of SIUP services, but based on preliminary research conducted by researchers, it shows that the level of responsiveness of the East Luwu Regency DPMPTSP is still not optimal, being in the